Sexual Assault and Trauma as Reflected in Amadu Maddyâ€™s â€œNo Past No Present No Futureâ€ (1973) and Zakes Mdaâ€™s â€œThe Madonna of Excelsiorâ€ (2002) - Abera Kassaw; Melakneh Mengistu (Universitas Airlangga, 2023)
This study aims to analyze the causes of sexual violence and conduct a critical examination of the traumatic impact of sexual violence as portrayed in Amadu's novel